Analysis of the Da'wah Message Content on Instagram Account @halimahalaydrus December 2025 Edition: English - Wahyuni Pulungan; Muhammad Husni Ritonga (Jurnal Komunikasi dan Ilmu Sosial, 2026)
The evolution of social media has established Instagram as an effective platform for disseminating Islamic dakwah religious outreach. One account actively conveying these messages to the public is @halimahalaydrus. This study aims to examine the content and categorize the dakwah messages shared via the @halimahalaydrus Instagram account during December 2025. A descriptive qualitative approach utilizing content analysis was employed. The dataset comprises 21 posts collected through observation and documentation techniques. Data analysis involved reduction, presentation, categorization of messages, and conclusion drawing. The results indicate that the messages fall into four categories aqidah faith/creed six posts sharia Islamic law/practice five posts akhlaq morality/character eight posts and information regarding dakwah activities two posts. The akhlaq category is the most dominant, as the majority of posts address character building, emotional control, patience, and the cultivation of positive interpersonal relationships. The aqidah category focuses on strengthening faith in Allah SWT, while the sharia category emphasizes the practice of acts of worship. Meanwhile, the information category serves as a medium to communicate various dakwah activities to the public. In conclusion, the @halimahalaydrus Instagram account effectively utilizes social media for dakwah by sharing content that is communicative, educational, and relevant to the community's needs.